Spontaneous fractional Chern insulators in transition metal dichalcogenide moiré superlattices - Heqiu Li; Umesh Kumar; Kai Sun; Shi-Zeng Lin (Physical Review Research, 2021)
The Moiré superlattice realized in two-dimensional heterostructures offers an exciting platform to access strongly correlated electronic states. In this work, we study transition metal dichalcogenides (TMD) Moiré superlattices with time-reversal symmetry and nontrivial spin/valley-Chern numbers. Utilizing realistic material parameters and the method of exact diagonalization, we find that at a certain twisting angle and fractional filling, gapped fractional topological states, i.e., fractional Chern insulators, are naturally stabilized by simply introducing the Coulomb repulsion. In contrast to fractional quantum Hall systems, where the time-reversal symmetry has to be broken explicitly, these fractional states break the time-reversal symmetry spontaneously. We show that the Chern number contrasting in the opposite valleys imposes a strong constraint on the nature of fractional Chern insulator and the associated low-energy excitations.